2020
DOI: 10.1097/01.jaa.0000668820.22981.be
|View full text |Cite
|
Sign up to set email alerts
|

PA job availability in primary care during 2014 and 2016

Abstract: Objectives: The objective of this project was to evaluate demand for PAs by examination of job postings. We compared proportions of PAs in primary care with proportions of job postings in primary care in 2014 and 2016 and described job postings for PAs by specialty in 2014 and 2016. Methods: Internet job postings for PAs supplied by Burning Glass Technologies were evaluated for practice specialty. Job postings were compared with existing filled position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 96 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…This study adopted a unique methodology of using job ads to investigate current trends, demand and opportunities for doctoral prepared PA faculty. The data sets used were comprehensive and expected to reflect well over 80% of actual PA job openings [12,13,23]. Study limitations include self-reported data in the national PA faculty and program surveys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study adopted a unique methodology of using job ads to investigate current trends, demand and opportunities for doctoral prepared PA faculty. The data sets used were comprehensive and expected to reflect well over 80% of actual PA job openings [12,13,23]. Study limitations include self-reported data in the national PA faculty and program surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Job posting data for 2014 was obtained from one of the leading labor analytics firms Burning Glass Technologies (BGT) [12,13] and data for 2015-2020 was obtained from academic job search engines that included chroniclesvitae.com, HigherEDJobs, PAEA JOBS, monster. com, Indeed, CareerBuilder, Simply Hired, LinkedIn and glassdoor.com.…”
Section: Methodsmentioning
confidence: 99%
“…This study adopted a unique methodology of using job ads to investigate current trends, demand and opportunities for doctoral prepared PA faculty. The data sets used were comprehensive and expected to re ect well over 80% of actual PA job openings [12,13,23]. Study limitations include self-reported data in the national PA faculty and program surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Job posting data for 2014 was obtained from one of the leading labor analytics rms Burning Glass Technologies (BGT) [12,13] and data for 2016-2020 was obtained from academic job search engines that included chroniclesvitae.com, HigherEDJobs, PAEA JOBS, monster.com, Indeed, CareerBuilder, Simply Hired, LinkedIn and glassdoor.com. Job postings that were included in this study (inclusion criteria) were academic job postings for physician assistants (PA) and contained a job description, educational degree requirement or preference, and were located within the United States regions and divisions.…”
Section: Methodsmentioning
confidence: 99%